Synthesis And Characterization Of Superhydrophobic Alumina Membrane Via Chemical And Morphological Modification - Ahmad, Nor Aini (2013)
Hydrophobicity is commonly known to have “water repellent” feature on a surface. Although ceramic membranes possess superior mechanical strength, excellent chemical resistance and great thermal stability, the natural hydrophilic feature of ceramic membranes limits their applications. Membrane modification by silane grafting has been widely reported due to its ease of handling, but the growth of hydrophobic structure introduces additional resistance in mass transfer. The major aim of this study is to synthesis superhydrophobic membrane with minimum membrane resistance. The effects of (heptadecafluoro-1,1,2,2-tetra hydrodecyl) triethoxysilane (HFDS) concentration on mass transfer resistance of superhydrophobic alumina membrane is studied as well. Besides direct grafting on membrane, HFDS was grafted on the additional thin alumina films prepared by sol-gel method with calcinations or steam treatment in order to reduce pore blockage. Alumina supports were first directly grafted with different volume ratios HFDS in ethanol (0.1-2.5 ml of HFDS:50 ml of ethanol). The HFDS grafted membranes showed static water contact angle in the range of 85.84 o (0.1ml of HFDS) to 138.91 o (1.0 ml of HFDS). The increment of HFDS concentration, however, caused membrane pore blockage due to the penetration of HFDS chain.